ASSOCIATION BETWEEN EOSINOPHILIC SINUSITIS AND EOSINOPHILIC OTITIS MEDIA - Yoshikawa, Mamoru; Haruna, Sin-ichi; Otori, Nobuyoshi; Moriyama, Hiroshi (JIBI INKOKA TEMBO, 2003)
We compared the clinical course of patients with eosinophilic sinusitis and eosinophilic otitis media and patients with eosinophilic sinusitis unassociated with eosinophilic otitis media and assessed the association between the two and changes in the middle ear lesions after endoscopic sinus surgery. The subjects were 175 patients with eosinophilic sinusitis, in 19 (10.8%) of whom, 34 ears, it was associated with eosinophilic otitis media, with 3/4 exhibiting lesions in both ears. The CT images, endoscopic findings, nonspecific total IgE level (RIST method), antigen-specific IgE level, and ECP concentrations in blood and the surface layer of the mucosa of the middle nasal meatus were compared. However, no clear differences were found between the groups with and without eosinophilic otitis media, and thus no association was found between the severity of eosinophilic sinusitis and eosinophilic otitis media. At 4 months after endoscopic sinus surgery, both middle ear mucosa and eustachian tube function had improved in parallel with the improvement in the sinus mucosa, and maintaining the paranasal sinuses in good condition was shown to be efficacious in improving the pathology of eosinophilic otitis media. However, when more than a year had passed since surgery, viscous otorrhea developed in the cases in which deterioration of the mucosa of the ethmoid sinus was observed, and eustachian tube function tended to deteriorate. Based on these results, repeatedly performance of local therapy that favorably maintains sinus lesions whenever eosinophilic sinusitis worsens appeared to be important as a means of controlling eosinophilic otitis media long-term.